2018
DOI: 10.1111/jfbc.12748
|View full text |Cite
|
Sign up to set email alerts
|

Moringa oleiferaseed oil or virgin coconut oil supplementation abrogates cerebral neurotoxicity induced by antineoplastic agent methotrexate by suppression of oxidative stress and neuro‐inflammation in rats

Abstract: Methotrexate (MTX) is an effective antineoplastic drug associated with wide organ toxicity. Accumulating evidence implicates oxidative stress to be a leading underlying mechanism of MTX‐induced neurotoxicity. The study explores antioxidant potential of virgin coconut oil (VCO) or Moringa oleifera seed oil (MOO) in MTX‐induced oxidative stress‐mediated cerebral neurotoxicity and inflammation in rats. Rats treated with VCO or MOO (5 ml/kg bw) for 17 days were administered MTX (20 mg/kg, intraperitoneally) on day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 48 publications
9
28
0
Order By: Relevance
“…Previous studies (Famurewa et al., 2019; Sheikh et al., 2014) confirmed that toxicity of methotrexate is associated with elevated inflammatory cytokine production. In this study, methotrexate increased the production of IL‐1β.…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies (Famurewa et al., 2019; Sheikh et al., 2014) confirmed that toxicity of methotrexate is associated with elevated inflammatory cytokine production. In this study, methotrexate increased the production of IL‐1β.…”
Section: Discussionmentioning
confidence: 83%
“…The findings of the other study stated the animals receiving cisplatin the levels of IL-10 decreased [33]. While IL-10 gene expression regained to normal level with administration of Moringa with cisplatin to normal level due to moringa decrease inflammation and oxidative stress caused by cisplatin corresponding to the findings have revealed that Moringa prevent oxidative stress-mediated toxicity in the brain tissue, testis, liver, and kidney of rats [34][35][36]. Moringa leaves extracts have a powerful antioxidant action against free radicals, prevent oxidative damage to major biomolecules and provide substantial protection against oxidative damage [37][38].…”
Section: Discussionmentioning
confidence: 88%
“…Previous works [42,43] reported that MTX toxicity increased the inflammatory cytokine production and the ROS generation. Here, MTX induced proinflammatory responses, as it upregulated the expression of IL-1β, IL-6, TNF-α, and IL-10 and downregulated the IFN-c expression.…”
Section: Discussionmentioning
confidence: 89%